Economic Effects of Regional Energy System Transformations: An Application to the Bavarian Oberland Region - Ana Maria Montoya Gómez; Marie-Theres von Schickfus; Markus Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper analyzes the effects of different energy transition paths on regional value added and on employment. We extend traditional input-output analysis by taking into account the scarcity of factors of production, and construct a dataset incorporating the regional dimension and specific electricity producing technologies. We find that the three observed districts in the German Oberland region benefit (to varying degrees) from investments towards regional energy transition, both in terms of additional value added and employment. Yet, the positive development comes at the expense of value added and employment in the rest of the country. Moreover, our analysis shows that medium-skilled employment increases most across all scenarios. This finding deserves attention in light of the current shortage of medium-skilled labor in Germany.
Keywords: Q43; R15; C67; 330